COMMUNICATION CHALLENGES AND INSTRUCTIONAL STRATEGIES FOR TEACHING ENGLISH TO MULTILINGUAL STUDENTS IN NIGERIA - Faith, Olagunju Edijana Bose; Emuobosa, Ivwighren Hannah (The Indonesian Journal of Social Studies, 2025)
This study investigates the communication obstacles that English language educators of multilingual classrooms experience in Delta State Nigeria. Research follows a descriptive survey design under Communicative Language Teaching (CLT) theory to study 180 lecturers working with English and Mass Communication departments in six Delta state tertiary institutions through structured questionnaires. Stratified random sampling allowed the investigation of perceived communication issues as well as the analysis of existing teaching methods and professional development workshop performance. The study discovered that instructors dealing with language differences experience major communication issues which affect their teaching performance. Workshops produce varied outcomes regarding their benefit to instructors because content delivery interacts with institutional backing as well as workshop design. The research shows that multilingualism creates major difficulties for English language education requiring better institutional backing. The implementation of peer collaboration and mentorship programs and multilingual resource-sharing systems should become part of the plan to provide teachers with effective teaching methods.